Causality Between Exchange Rate Fluctuation and Export Volume in Nigeria - Okeke, Onyinye Rita; Okeke, Daniel C (Social Science Research, 2022)
The study investigated the causality between Naira exchange rate (EXR) and export volume (EX) in Nigeria. Economic researchers and policy makers have been concerned about the significant impact of exchange rate fluctuations on the economy in general and trade, in particular. However, theoretical and empirical works on the subject have produced mixed results. This study used annual data spanning from 1983 to 2020. Applying the econometrics tools of unit root test, co-integration, error correction model (ECM) and pair-wise Granger causality test, EX became stationary at first differencing whereas EXR became stationary at level. The co-integration test identified two co-integrating equations. The ECM result is negative and significant as desired. The Granger causality test shows a uni-directional causality flowing from exchange rate to export which may imply that a change in exchange rate will bring about change in the export volume, holding other factors constant which may imply that a fall in the currency value of the country makes export cheaper, ceteris paribus, while no causality running from EX to EXR. Nigeria, as a country which its only major exportable is crude oil, export may not deeply be a major factor that affects the variations in exchange rate as there are many other factors that could be responsible for the fluctuations. This study recommended a flexible but favorable naira exchange rate, diversification in all sectors of the economy and employment of sustainable trade policies that will promote exportation and trigger economic growth.